Spatial distribution, prevalence, and determinants of unintended pregnancy among youth (15–24) in Ethiopia: Further analysis of Ethiopia Demographic and Health Survey - Sewnet Adem Kebede (SAGE Publishing, 2021)
Objectives: This study aimed to determine the spatial distribution, prevalence, and determinant factors of unintended pregnancy among youth in Ethiopia. Methods: Using the Ethiopian Demographic and Health Survey 2016, a total of 2446 pregnant women aged 15–24 in the last 5 years, including current pregnancy, were included in the study. The unintended pregnancy data were spatially visualized using coordinates for each respondent in the survey using ArcGIS 10.3. The Bernoulli model was used to identify the presence of purely spatial unintended pregnancy cluster using SaTScan software. Logistic regression analysis was fitted to determine factors associated with unintended pregnancy among youth. Results: Unintended pregnancy among youth had spatial variation across the country. Among youth, 20.5% (confidence interval: (19.0, 22.2)) of pregnancies were estimated to be unintended. Spatial scan statistics identified 72 primary clusters (log-likelihood ratio of 37.6, at p  < 0.001) which were located in Addis Ababa, southern part of Amhara, northwest of Oromia and northeast of Southern Nations, Nationalities and Peoples Region. Age, region, marital status, occupation, sex of household head, and number of household members were the determinant factors of unintended pregnancy among youth in Ethiopia. Conclusion: The distribution of unintended pregnancy among youth in Ethiopia was nonrandom. Unintended pregnancy prevention strategies among youth need to be targeted on the identified factors. Hence, we recommend creating awareness on sexual and reproductive health rights with special priority to the identified hotspot areas (Amhara, Addis Ababa, Gambella, Northern part of Southern Nations, Nationalities and Peoples Region, and northwest of Oromia region) to reduce unintended pregnancy.